ВЕБ СЕРВИСЛЕР ЖӘРДЕМИНДЕ ОҚЫЎШЫЛАРДЫҢ БИЛИМЛЕРИН БАҲАЛАЎ ҲӘМ АНАЛИЗЛЕЎ ИМКАНИЯТЛАРЫ - Кутлымуратова, Д.A.; Турдышов, Д.Х. (FAN va JAMIYAT, 2023)
This article talks about increasing the informational competence of the teacher, evaluating and analyzing the knowledge of students using web services, as well as methods of effective use of web services in determining and evaluating the acquired knowledge and skills of students.